2022
DOI: 10.21203/rs.3.rs-1453873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ICA1 is differentially methylated and expressed in familial type 1 diabetes

Abstract: There has recently been a growing interest in examining the role of epigenetic modifications, such as DNA methylation, in the etiology of type 1 diabetes (T1D). This study aimed to delineate differences in methylation patterns between T1D-affected and healthy individuals by examining the genome-wide methylation of individuals from three Arab families from Kuwait with T1D-affected mono-/dizygotic twins and non-twinned siblings. Bisulfite sequencing of DNA from the peripheral blood of affected and healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Interestingly, our study highlights ONECUT1 methylation as a potential marker for MODY-X, representing either a unique subtype of MODY or a form of diabetes that is yet to be classified. In this context, it is important to point out that our previous study (Dashti et al, 2022) did not find ONECUT1 as one of the observed differentially methylated and expressed genes in familial T1D. Thus, the observed ONECUT1 methylation in the MODY patients in this study can help to clarify when suspected MODY individuals are misdiagnosed as T1D patients.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Interestingly, our study highlights ONECUT1 methylation as a potential marker for MODY-X, representing either a unique subtype of MODY or a form of diabetes that is yet to be classified. In this context, it is important to point out that our previous study (Dashti et al, 2022) did not find ONECUT1 as one of the observed differentially methylated and expressed genes in familial T1D. Thus, the observed ONECUT1 methylation in the MODY patients in this study can help to clarify when suspected MODY individuals are misdiagnosed as T1D patients.…”
Section: Discussionmentioning
confidence: 49%
“…Secondly, the peripheral blood sample is not the ideal biological sample as a) it contains a diverse mixture of cells and DNAm is cell-specific, and b) it may harbour DNA methylation events due to pathological differences relating to autoimmune processes that we could not consider for adjusting the results of differential methylation analysis. However, blood as biological sample has been used in other DNA methylation studies on diabetes (Disanto et al, 2013;Agardh et al, 2015;Johnson et al, 2020;Dashti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation